Pelaksanaan Pemeliharaan Sarana dan Prasarana Pendidikan pada Madrasah Ibtidaiyah - Tirta Mulyadi; Iswahyu Pranawukir; Rina Sovianti; Ahmad Fadil Mediwinata; Afif Alfiyanto; Fitri Hidayati (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2022)
This study aims to analyze the implementation of the maintenance of educational facilities and infrastructure at MI Nurul Ulum and analyze the factors that influence it. In this study, the researcher used a qualitative research type using a qualitative descriptive approach. The research data were collected using the method of observation, interviews, and documentation. The techniques used in data analysis are data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of the maintenance of educational facilities and infrastructure at MI Nurul Ulum can be said to be quite good in terms of the indicators of the implementation of the maintenance of educational facilities and infrastructure, namely coordination, motivation, communication and direction. The implementation that has been carried out has been considered quite good although there are still shortcomings in the implementation of the maintenance of these facilities and infrastructure. Therefore, in the implementation of the maintenance of facilities and infrastructure, it should be further improved in order to achieve the previously planned goals. The supporting factors for the implementation of the maintenance of educational facilities and infrastructure are school facilities, recording of facilities and infrastructure, the role of school committees, and teacher involvement. While the inhibiting factors are the lack of budget, limited human resources in accordance with their fields, and goals that are less focused.